2021
DOI: 10.1002/acm2.13212
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a potential source of error for 6FFF beams delivered on an AgilityTM multileaf collimator

Abstract: Purpose: The performance of the Agility TM multileaf collimator was investigated with a focus on dynamic, small fields for flattening filter free (FFF) beams. Methods: In this study we have developed a simple tool to test the robustness of the control mechanisms during dynamic beam delivery for Elekta's VersaHD linear accelerator with Integrity 4.0.4 control software. We have programed the planning system to calculate dose for delivery of sweeping gaps. These sweeping gaps have a constant speed, constant size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…
Dear Editor, We read with interest the letter to the editor written by Foy et al 1 regarding a recently published article on 6 FFF beams delivered on an Agility multileaf collimator (MLC). 2 We appreciate the interest in this publication by the authors; however, after careful review we have identified several apparent misunderstandings in the letter to the editor by Foy et al The assertions presented by Foy et al do not specifically pertain to our article as the data discussed in their letter do not relate directly to the purpose of the cited article. 2 Specifically, we would like to correct the following misinterpretations by Foy et al:
…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…
Dear Editor, We read with interest the letter to the editor written by Foy et al 1 regarding a recently published article on 6 FFF beams delivered on an Agility multileaf collimator (MLC). 2 We appreciate the interest in this publication by the authors; however, after careful review we have identified several apparent misunderstandings in the letter to the editor by Foy et al The assertions presented by Foy et al do not specifically pertain to our article as the data discussed in their letter do not relate directly to the purpose of the cited article. 2 Specifically, we would like to correct the following misinterpretations by Foy et al:
…”
mentioning
confidence: 93%
“…1 It was shown by Lorenz and Paris that Monaco's sequencer can generate a relatively high proportion of 3.5 mm leaf apertures in complex VMAT plans. 2 The extent to which small gaps exist and affect a facility's assemblage of plans will depend upon the TPS and plan complexity. The assumption by Foy et al that "3.5 mm will not necessarily be found in most clinical plans" 1 may not be universally valid.…”
mentioning
confidence: 99%
“…Additionally, the Agility TM MLC requires a gap between corresponding leaves of 5 mm when projected at isocenter. Therefore, the dose errors reported by Lorenz and Paris 1 for field sizes smaller than 3.5 mm will not necessarily be found in most clinical plans. This limitation in leaf gap width may also be a source of discrepancy.…”
mentioning
confidence: 95%
“…A recent publication by Lorenz and Paris 1 “Identification of a potential source of error for 6 FFF beams delivered on an Agility TM multileaf collimator” reported on discrepancy between calculated and measured doses to be 10% and 60% at isocenter for a 3.5‐mm and 1‐mm gap field size, respectively. The investigators attempted to determine the cause of the relatively high failure rates during their patient‐specific quality assurance (PSQA) when using flattening filter‐free (FFF) photon beams.…”
mentioning
confidence: 99%
See 1 more Smart Citation